Measurement of quarkonium production cross sections in pp collisions at s=13TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Elsevier BV, 2018)
Differential production cross sections of prompt J/ψ and ψ(2S) charmonium and Υ(nS) (n = 1, 2, 3) bottomonium states are measured in proton-proton collisions at √ s = 13 TeV, with data collected by the CMS detector at the LHC, corresponding to an integrated luminosity of 2.3 fb−1 for the J/ψ and 2.7 fb−1 for the other mesons. The five quarkonium states are reconstructed in the dimuon decay channel, for dimuon rapidity |y| < 1.2. The double-differential cross sections for each state are measured as a function of y and transverse momentum, and compared to theoretical expectations. In addition, ratios are presented of cross sections for prompt ψ(2S) to J/ψ, Υ(2S) to Υ(1S), and Υ(3S) to Υ(1S) production.